Pengembangan Trainer KIT Mikrokontrol Arduino Uno Berbasis IOT sebagai Media Penunjang Pembelajaran Sistem Kontrol Terprogram - Harahap, Partaonan; Affandi; Fauzi, Rahmat; Nasution, Arya Rudi; Faisal, Ade; Oktrialdi, Benny (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Learning media training is one of the important factors in improving learning outcomes, with learning media that suits the needs, especially students of SMK Teknologi Yayasan Pendidikan Sinar Husni can understand learning. The purpose of the implementation of the community partnership program (PKM) is to produce interactive learning media that is valid, practical and effective to help students of SMK Teknologi master the field of Electronics and Control. Method: The method for implementing Community Partnership Service activities for SMK Teknologi Yayasan Pendidikan Sinar Husni, Department of Electrical Engineering / Electricity, is by first making observations to the location of the School where the Community Service is held, as well as sharing with several Electrical Engineering teachers. This is done to identify service methods that are in accordance with the conditions of the Community Partnership Service Team Partners in the field, so that later it will be right on target. Result: This activity can make and understand basic Arduino Uno learning media and implement it well. Conclusion: It is hoped that in the future this activity can inspire and motivate the participants and can innovate in the development of science and technology in the world of Electronics and Control Instrumentation to support the Industrial Revolution 4.0 program.